Legal environment of business in the information Age - Baumer, David L (McGraw-Hill, 2004)
Part 1 The Structure of the Legal Environment 1. The Legal Environment of Business in the Information Age Appendix: How to Brief a Case and What Does All That Stuff Mean? 2. The Court System and Jurisdiction 3. The Litigation/Trial Process 4. Alternative Dispute Resolution 5. Application of Constitutional Law to Business 6. Government Regulation of Business and Ethics Part 2 The Common Law and Interfaces with the Internet 7. Basic Contract Law 8. Commercial Law: The Uniform Commercial Code (UCC) 9. Current and Future Contract Law for E-Commerce 10. Torts: Wrongs and Their Remedies 11. Cybertorts, Privacy, and Government Regulation 12. Property: Real, Personal, and Intellectual 13. Copyright, Trademark, and Protection of Software 14. Business Organization and Cybercompanies Part 3 Government Regulation 15. Agency, Electronic Agents and Employment at Will 16. Employment Law and Protection of Workers 17. Antidiscrimination Legislation 18. Consumer Protection and Electronic Transactions 19. Antitrust and the Interface with Intellectual Property 20. Government Regulation of Securities and Online Trading 21. Environmental Law 22. Computer Crime: Pornography, Fraud, Hacking and Gambling 23. Real Space and Cyberspace: Jurisdiction, Taxation, and International Law Issues A: The Constitution of the United States of America B: Excerpts from The Digital Millennium Copy right Act of 1998 C: Excerpts for the E-SIGN Act; Quỹ Châu Á